2013
DOI: 10.1080/00087114.2013.857829
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic and anti-genotoxic effect of aqueous extracts ofSpondias mombinL.,Nymphea lotusL. andLuffa cylindricaL. onAllium ceparoot tip cells

Abstract: Spondias mombin L., Nymphea lotus L. and Luffa cylindrica L. are commonly used in the traditional management of cancer in Nigeria. The genotoxic and anti-genotoxic effects of aqueous extracts of these plants was evaluated using the Allium cepa L. assay. Onion bulbs were exposed to 0.5-10 mg ml-1 concentrations (v/v) of each extract, prepared as practiced locally, for analyses of root growth inhibition and induction of cytogenetic damage, respectively. There was concentration-dependent, significant (p < 0.05) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 34 publications
2
22
0
1
Order By: Relevance
“…Genotoxic and antigenotoxic effects of plant extracts have been evaluated using various genotoxicity tests and experimental organisms (Oyeyemi and Bakare, 2013;Munari et al, 2014;Vijaya et al, 2014). Among vertebrates models, rats (Rattus norvegicus, particularly the albino Wistar and Sprague-Dawley rats) and mice (Mus musculus, particularly the Swiss albino mice) are most important experimental organisms in toxicology and genotoxicology studies, because of an extensive body of knowledge of physiological mechanisms, and cellular and molecular similarity to humans (Vogt, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Genotoxic and antigenotoxic effects of plant extracts have been evaluated using various genotoxicity tests and experimental organisms (Oyeyemi and Bakare, 2013;Munari et al, 2014;Vijaya et al, 2014). Among vertebrates models, rats (Rattus norvegicus, particularly the albino Wistar and Sprague-Dawley rats) and mice (Mus musculus, particularly the Swiss albino mice) are most important experimental organisms in toxicology and genotoxicology studies, because of an extensive body of knowledge of physiological mechanisms, and cellular and molecular similarity to humans (Vogt, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, we compared the effect of an organic (Selol) and inorganic (sodium selenate (IV)) form of selenium, using the Allium plant test. The test is widely used in arrays of cytotoxicity of various substances, such as heavy metals, hormones, nanoparticles or potential anticancer drugs (Grant 1982;Oyeyemi and Bakare 2013;Pesnya 2013;Firbas and Amon 2014). Cells of the test contain a small number (16) of large chromosomes, which facilitates measurements of cytological parameters such as cell mitotic activity, type and frequency of aberrations and disturbances of cell divisions (Nielsen and Rank 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The small number (16) of large chromosomes allows easy analysis of aberrations and mutagenic changes. For this reason, it is often used in screening tests and analyses of potential anticancer drugs with respect to their cytotoxicity and cytostatics, and the effects of pathogens, nanoparticles and environmental pollutions (Majewska et al 2000;Gabara et al 2006;Kuraś et al 2006;Oyeyemi and Bakare 2013;Pesnya 2013;Firbas and Amon 2014). Our investigations compared the effect of both forms of selenium on structure of nuclei and chromosomes and the mitotic activity of Allium test cells.…”
Section: Introductionmentioning
confidence: 99%
“…The A. cepa test has been used to detect a variety of environmental pollutants in industrial wastewater and the results obtained were reported significant versus control (Leme and Marin-Morales, 2009). A number of studies have been performed using A. cepa test system and positive responses of A. cepa have been reported i.e., complex mixture (Aguiar et al, 2016;Andrade-Vieira et al, 2012;Blagojević et al, 2009;Chakraborty and Mukherjee, 2010;Chakraborty et al, 2009;Klauck et al, 2013;Mazzeo et al, 2011b;Pathiratne et al, 2015;Pekol et al, 2012;Vidaković et al, 1993;Yahaya et al, 2012), antitoxic agent (Aslantürk and Çelik, 2006;Frescura et al, 2012;Kuhn et al, 2015;Kumari et al, 2013;Majewska et al, 2003;Nantes et al, 2014;Oyeyemi and Bakare, 2013;Santana et al, 2016;Ślusarczyk et al, 2014;Ślusarczyk et al, 2016;Sultan and Çelik, 2009), contaminated soil (Christofoletti et al, 2013;Dash et al, 1988;Kataeva et al, 2012;Kopliku and Mesi, 2012b;Masood and Malik, 2013a;Meier et al, 1997;Oberholster et al, 2008;Paul et al, 2013;Saxena et al, 2004;Sayles et al, 1999), drugs (Firbas and Amon, 2014;Grisolia and Takahashi, 1991;Jos et al, 2003;…”
Section: Industrial Wastewater Naturementioning
confidence: 99%